ANALISIS DAMPAK LALU LINTAS AKIBAT PENGOPERASIAN TAMAN RAMA SCHOOL - Putu Alit Suthanaya; Dewa Made Priyantha Wedagama; I Gusti Bagus Satriyadi (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
ANALYSIS OF TRAFFIC IMPACT DUE TO OPERATION OF RAMA PARK SCHOOL ABSTRACT Taman Rama School which has 1144 students is included in the mandatory traffic impact analysis based on the Minister of Transportation Regulation No. PM 75 of 2015 concerning the Implementation of Traffic Impact Analysis. Data are analyzed by the formulas and methods of the Indonesian Road Capacity Manual 1997, assisted by using CONTRAM software. The analysis output showed a trip production of 413 pcu/hour and a trip attraction of 632.8 pcu/hour during peak hours. The performance of the road and intersection are improving as the result of the stop and go restriction on the road and the availability of the school transportation assuming 50% of students will switch from private vehicles. With the handling, in the existing year V/C Ratio at Jalan Cokroaminoto I improved to 0.72, Jalan Cokroaminoto II to 0.7, Jalan Cokroaminoto III to 0.67, Jalan Gunung Galunggung to 0.38, and Jalan Ken Dedes to 0.72, while the Cargo intersection performance as seen from the average intersection delay improved to 97.541 seconds/pcu, and the degree of saturation (DS) at the intersection of Ken Dedes also improved to 0.59. It's expected in the planned year (2023) there will be traffic performance improvement when compared without the handling, namely V/C Ratio Jalan Cokroaminoto I to 0.81, Jalan Cokroaminoto II to 0.937, Jalan Cokroaminoto III to 0.76, Jalan Gunung Galunggung to 0.42, and Jalan Ken Dedes to 0.81, while the performance of Cargo intersection seen from the average intersection delay also improved to 161.02 seconds/pcu and the degree of saturation of Ken Dedes intersection to 0.66. Parking lots capacity provided by Taman Rama School is still beyond number of the needs, where the availability of 179 SRP motorbikes and 107 SRP cars still excessive to the highest usage of 90 SRP cars and 154 SRP motorbikes. Based on PV2 values, the type of suitable crossing facilities for the locations,covers in front of the school and in front of the additional parking area is Pelican Crossing.